FUNGSI DEWAN PERWAKILAN RAKYAT DAERAH DALAM PENGAWASAN PELAYANAN PUBLIK DI KABUPATEN SITUBONDO - Khairil Anwar; Bambang Supriyono; Suryadi . (Universitas Tribhuwana Tunggadewi, 2015)
Abstract :The function of supervision is the authority of the House of Assembly (DPRD) especially when it must do supervision over the implementation of local regulation and other rules, the usage of APBD, the policy making and performance of local government in organizing local development, and the execution of international cooperation in locality. Being main stakeholder in local public service, DRPD is expected to stimulate the improvement of public service quality. In reality, the mechanism to implement the function and task of supervision of DPRD over the government of Situbondo Regency is not systematic. One reason is that there is no legal base for technical guide of supervision system. The committees in DPRD of Situbondo have undergone the supervision over local government but their supervision is not focusing upon their performance on task field of the committee. The supervision by the committee is a merely routine, not touching the core of problem, and still away from giving concrete solution. The implementation of task and function of supervision in DRPD of Situbondo Regency over the government (Local Leader), therefore, must be supported by strong legal base, adequate fund to facilitate task and function implementation, and reliable facility, structure and infrastructure, as well as the sufficient backup from the secretariat of DPRD. Research method is qualitative. Analysis technique is Miles & Huberman’s interactive analysis model.